Presentation - Mansilla, Ricardo (INTER DISCIPLINA, 2018)
The history of our civilization, which according to K. Marx has been the history of the class struggle, has had an ubiquitous element in all its stages, the violent resolution of conflicts between human groups. Wars have been the inseparable companions of humanity’s journey through all their long and tortuous development. Thus, each interval of peace between conflicts seems like an oasis where human beings are repaired from the traumas of the previous conflict, vow not to fall back into the temptation of violence and end up justifying without remedy the relevance of the next conflict. As Aeschylus said, truth is the first victim of all war. All of the above confirms the convenience of analyzing the phenomenon of peace in the broadest possible context. This number is undoubtedly a remarkable contribution to this effort. In the pages of his dossier, readers will find a wide spectrum of interdisciplinary contributions to the different facets of this concept.